(3fXe GdCSHGH Hjf Gdfaj hGdGYJbGOs - (3HdYeT Hf eMeO eHGQc GdaGVdj GdGjHjQj,J (B1210 (3g` s ((3YHO Gddg Hf CMeO Hf GdQGRi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi GdCMjOi eMeO GdgGOi Edi GdJhMjO ai GdPGJ hGdhUa heKd TGgO Udi hSde Ydjg GdhGMO hHYO aGdQSd hGdCfHjGA GdYXGe hGdChdjGA hGdUMGHI GdcQGe s
(3BNQgG (B:s
(3aGdegOi GdLGeY Hjf Pjf hGdZjQ bO jVd Ohf ejf bO Je eG jfLi ef GdTQc GdNai aGZaQ dbGQFg QH hGQCa hUd jG QH hSdeG Ydi GdPi bO aGb cd ef SeGg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeO RQhb Hf HdYeT (B- (3NGUI s
Keywords: (3GdJhMjO hGdedd hGdfMds